(untitled) (Agroindustria, Sociedad y Ambiente, 2019)
Since man began his evolutionary process, he undertook a journey like no other, where sensations and emotions have been determining and responsible for his actions. This essay aims to analyze the conception of emotions from rational scientific epistemology, in contrast to the theoretical positions that have marked history in Western philosophy. Knowing the context, from both positions, a set of contributions is established that lead to establishing the relevance of emotional recognition, as a key element in the education of an integral, conscious and responsible individual of their own social actions and actions.